Inflammatory bowel disease an evidence-based practical guide - Hart, Ailsa L.; Ng, Siew Chin (Tfm Pub., 2012)
A pocket handbook on the practical and safe use of drugs in inflammatory bowel disease to achieve best patient outcome in day-to-day practice.